半導体ナノ粒子複合体、半導体ナノ粒子複合体分散液、半導体ナノ粒子複合体組成物および半導体ナノ粒子複合体硬化膜 (2024)
Provided is a semiconductor nanoparticle complex in which two or more kinds of ligands including a ligand I and a ligand II are coordinated to a surface of a semiconductor nanoparticle. The ligands are each an organic ligand including an organic group and a coordinating group. The ligand I is a thiocarboxylic acid represented by the following general formula (1). The mole fraction of the ligand I in the ligands is 0.2 mol % to 35.0 mol %.General formula (1):HS-X-(COOH)n  (1)(In general formula (1), X is a (n+1)-valent hydrocarbon group, and n is a natural number of 1 to 3.) The present disclosure provides a semiconductor nanoparticle complex dispersible at a high mass fraction in a dispersion medium having polarity while a high fluorescence quantum yield (QY) of the semiconductor nanoparticle is retained.